(untitled) (Stato, Chiese e pluralismo confessionale, 2013)
Le texte, déjà publié dans la Revue des Droits de l’Homme (Lettre “Actualités Droits-Libertés” du CREDOF, 11 juin 2013), est reproduit avec l’aimable autorisation de l’Auteur et l’Editeur. SOMMAIRE: 1. Introduction - 2. Une issue retentissante: la concrétisation d’une protection conventionnelle contre les persécutions religieuses - 3. Un raisonnement parcellaire: les apories de l’analyse européenne à l’aune de la liberté de religion - 4. Conclusion - 5. Jurisprudence liée - 6. Appendice. ABSTRACT: By banning deporting of a coptic christian by France to Egypt, where he might suffer persecution, European court of human rights has made an important contribution to the protection of foreigners against measures involving expulsion. The European solution is important because it deals with a complex, but crucial, concept: religious persecution. Unfortunatly, the opportunity offered by this case hase not been fully exploited. Freedom of religion was at the heart of this case, but European court did’nt use it enough.